2009
DOI: 10.1016/j.bbr.2009.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress, corticosterone, and epinephrine administration on learning in place and response tasks

Abstract: These experiments examined the effects of prior stress, corticosterone, or epinephrine on learning in mazes that can be solved efficiently using either place or response strategies. In a repeated stress condition, rats received restraint stress for 6 h/day for 21 days, ending 24 h before food-motivated maze training. In two single-stress conditions, rats received a 1-h episode of restraint stress ending 30 min or 24 h prior to training. Single stress ending 30 min prior to training resulted in a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 96 publications
(180 reference statements)
3
28
0
3
Order By: Relevance
“…The present study identified a pattern suggesting that a larger proportion of rats exposed to CVS used habitual (i.e., stimulus-response) strategies, whereas a larger proportion of non-stressed rats used spatial strategies. These findings, while not statistically significant, demonstrate a similar pattern as those found by others (Sadowski et al, 2009). Sadowski and colleagues (2009) tested rats on a modified version of the Dual Solution T-maze, wherein the number of trials to learn either the spatial (place) version or the habitual (response) version of the task were measured.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study identified a pattern suggesting that a larger proportion of rats exposed to CVS used habitual (i.e., stimulus-response) strategies, whereas a larger proportion of non-stressed rats used spatial strategies. These findings, while not statistically significant, demonstrate a similar pattern as those found by others (Sadowski et al, 2009). Sadowski and colleagues (2009) tested rats on a modified version of the Dual Solution T-maze, wherein the number of trials to learn either the spatial (place) version or the habitual (response) version of the task were measured.…”
Section: Discussionsupporting
confidence: 92%
“…These findings, while not statistically significant, demonstrate a similar pattern as those found by others (Sadowski et al, 2009). Sadowski and colleagues (2009) tested rats on a modified version of the Dual Solution T-maze, wherein the number of trials to learn either the spatial (place) version or the habitual (response) version of the task were measured. These authors found a less robust but similar pattern, in that rats exposed to chronic restraint stress (6h/d/21d) required a greater number of trials to learn the spatial task as compared to non-stressed control rats (Sadowski et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations